Heparin-induced thrombocytopenia - Greinacher, A.; Althaus, K.; Krauel, K.; Selleng, S. (Hämostaseologie, 2010)
Heparin-induced thrombocytopenia (HIT), typically occurring in the second week of heparin therapy, is an antibody-mediated adverse drug reaction associated with increased thrombotic risk. The most important antigens are located on platelet factor 4 (PF4)/heparin complexes. HIT is always caused by platelet-activating antibodies, but not all PF4/heparin-reactive antibodies cause HIT. Thus, tests have a high negative, but only a moderate, positive predictive value. Clinical suspicion of HIT requires cessation of heparin and substitution with an alternative anticoagulant. As these drugs have an increased bleeding risk, they should be used in therapeutic doses only if HIT is considered very likely. Avoiding/postponing coumarin is crucial in minimizing microthrombotic complications. Recent studies of HIT immunobiology suggest that HIT mimics immunity against repetitive antigens, as are relevant in microbial defense. Thus, understanding HIT may help unravel why host defenses can trigger autoimmunity.
Keywords: Heparin; heparin-induced thrombocytopenia; platelets; pathogenesis; immunology; anticoagulants